‘In New Zealand I feel more confidence’: The role of context in the willingness to communicate (WTC) of migrant Iranian English language learners - Cameron, Denise (International Journal of English Studies, 2015)
This article will discuss recent theories of Willingness to Communicate (WTC) and provide an overview of studies into this individual difference which have been conducted in both Iran and New Zealand (NZ). So far few qualitative studies have been carried out into WTC or have used permanent migrants as participants. The article reports on a longitudinal study of the WTC of a group of Iranian migrants to NZ. By means of questionnaires, observations, and individual semi-structured interviews conducted at six-month intervals, case studies of these learners in a NZ university English class were compiled. Their WTC was found to encompass such learner characteristics as confidence, motivation, and personality, and varied from country to country and semester to semester. Finally, this article discusses the contribution of this study to the WTC field of research, identifying the implications of these results for teachers of English in the ESL (English as a Second language/migrant) context and possible avenues for future research.